Investigation of 3.3 kV 4H-SiC DC-FSJ MOSFET Structures - Chen, Chia-Yuan (Micromachines (Basel), 2021)
This research proposes a novel 4H-SiC power device structure—different concentration floating superjunction MOSFET (DC-FSJ MOSFET). Through simulation via Synopsys Technology Computer Aided Design (TCAD) software, compared with the structural and static characteristics of the traditional vertical MOSFET, DC-FSJ MOSFET has a higher breakdown voltage (BV) and lower forward specific on-resistance (R(on,sp)). The DC-FSJ MOSFET is formed by multiple epitaxial technology to create a floating P-type structure in the epitaxial layer. Then, a current spreading layer (CSL) is added to reduce the R(on,sp). The floating P-type structure depth, epitaxial layer concentration and thickness are optimized in this research. This structure can not only achieve a breakdown voltage over 3300 V, but also reduce R(on,sp). Under the same conditions, the Baliga Figure of Merit (BFOM) of DC-FSJ MOSFET increases by 27% compared with the traditional vertical MOSFET. R(on,sp) is 25% less than that of the traditional vertical MOSFET.